Long-term survival of patients with prostate cancer in Martinique: Results of a population-based study. (April 2019) - Joachim, Clarisse; Ulric-Gervaise, Stephen; Dramé, Moustapha; Macni, Jonathan; Escarmant, Patrick; Véronique-Baudin, Jacqueline; Vinh-Hung, Vincent
Highlights: We evaluated invasive prostate cancer diagnosed in Martinique between 2005 and 2014. We analysed age at diagnosis, risk of disease progression and treatments of prostate cancer patients. This study provides long term data regarding cancer management in Martinique. Abstract: Background: Martinique has one of the highest incidences of prostate cancer (PCa) worldwide. We analysed overall survival (OS) among patients with PCa in Martinique, using data from a population-based cancer registry between 2005 and 2014. Methods: The log-rank test was used to assess the statistical differences between survival curves according to age at diagnosis, risk of disease progression including Gleason score, stage at diagnosis and Prostate Specific Antigen (PSA). A multivariable Cox model was constructed to identify independent prognostic factors for OS. Results: A total of 5045 patients were included with a mean age at diagnosis of 68.1±9.0 years [36.0 – 98.0 years]. Clinical stage was analysed in 4999 (99.1% of overall), 19.5% were at low risk, 34.7% intermediate and 36.9% at high risk. In our study, 8.9% of patients with available stage at diagnosis, were regional/metastatic cancers. Median PSA level at diagnosis was 10.4 ng/mL. High-risk PCa was more frequent in patients aged 65-74 and ≥75 years as compared to those aged <65 years (36.6% and 48.8% versus 28.7% respectively; p<0.0001). One-year OS was 96.3%, 5-year OS was 83.4 and 10-year OS was 65.0%. Median survival was not reached in the whole cohort. High-risk PCa (HR=2.32; p<0.0001), regional/metastatic stage (HR= 9.51; p<0.0001) and older age (65-74 and ≥75 years - respectively HR=1.70; and HR=3.38), were independent prognostic factors for OS (p<0.0001). Conclusion: This study provides long term data that may be useful in making cancer management decisions for patients with PCa in Martinique.